Prediction Analysis of the Number of Outpatient Visits at the Internal Medicine Polyclinic at At-Turots Al-Islamy Hospital Yogyakarta - Firman, Firman; VIto, Ardanu; Tania Vergawita (Universitas Ahmad Dahlan, 2024)
Background : The COVID-19 outbreak crisis has had a significant impact on the continuity of health services in hospitals. The trend in the number of outpatient visits has decreased dramatically during the 2 years of the pandemic. This study aims to identify or predict the number of post-pandemic patient visits at the Internal Medicine Polyclinic at At-Turots Al-Islamy Hospital Yogyakarta. Methods: The research method is mixed, namely a combination of quantitative and qualitative research. The sampling technique uses purposive sampling with two main data sets; 1) Secondary data from medical records regarding internal medicine patients during the 2017-2021 period, and 2) In-depth interview data with three informants, namely management, doctors, and administrative staff. Analysis visit prediction using least squares. Results: The research results show that the average number of patient visits in 2017-2021 was 5,684 visits. Meanwhile, predictions of visits in 2022 will increase by x%, in 2023 they will increase by 14%, and in 2024 they will increase by 12%. Conclussions: Researchers assume that the increase in the number of patient visits could occur because the COVID-19 trend has decreased and government activity restrictions have been relaxed or no longer apply.